Emissions trading in the aviation and maritime sector: Findings from a revised taxonomy - Orestis Schinas; Niklas Bergmann (Cleaner Logistics and Supply Chain, 2021)
Market-Based Measures (MBMs) and especially emissions trading schemes (ETS) have been considered by the International Maritime Organization (IMO), as a supplementary set of initiatives to decarbonize international shipping. While respective decisions of the IMO are still pending, the global aviation industry has already accumulated experiences from ETS operations; hence the knowledge transfer is possible as this research field is largely unexplored. This paper aims to provide a detailed literature review of studies investigating the EU Emissions Trading System (EU ETS) for aviation and the Carbon Offsetting and Reduction Scheme for International Aviation (CORSIA) as well as to deliver a taxonomy of ETS design and its effects. The findings are then compiled and clustered according to the taxonomy and explored in detail. Moreover, this paper discusses findings of this taxonomy that could support further on MBM in international shipping, such as important implications, and provisions for carbon financial market design.